An ignition delay correlation for compression ignition engines fueled with straight soybean oil and diesel oil blends. (1st December 2019) - Nieto Garzón, Nury A.; Oliveira, Amir A.M.; Bazzo, Edson
Highlights: A correlation for ignition delay of soybean oil and diesel oil blends is proposed. Correlation includes the droplet Reynolds number and volume fraction of soybean oil. Experimental ignition delay was found from in-cylinder pressure measurements. Diesel engine was fueled with soybean oil, diesel oil and blends. Sensitivity analysis showed strong influence of soybean oil on the ignition delay. Abstract: A correlation to estimate the fuel ignition delay of a diesel engine operating with blends of straight soybean oil and diesel oil is proposed. Ignition delay measurements were carried out on a dynamometer bench using a 14.7 kW/2200 rpm single-cylinder compression ignition engine fueled with blends of 0%, 50%, 80% and 100% v/v straight soybean oil in commercial diesel oil (S10). The injection and ignition angles were determined from the second derivative of the in-cylinder pressure curve. A correlation was developed expressing the ignition delay data as a function of the droplet Reynolds number, global fuel/air equivalence ratio, in-cylinder gas temperature, and volume fraction of soybean oil. The non-dimensional parameters are obtained from the dimensions of the injector nozzle, liquid fuel and in-cylinder gas properties to generalize the applicability to other vegetable oils and engine operating conditions. The coefficient of determination (R 2 ) of the curve-fit was 0.8465 for a 95% confidence interval. Finally, a sensitivity analysis showed a significant influence of the in-cylinder gas temperature and volume fraction of soybean oil on the ignition delay.